Preservation, inoculum development and quality management of yeasts in the brewing industry - Morakile, Gontse (University of the Free State, 2001)
Techniques to maintain and preserve microorganisms have become important to ensure availability of microorganisms for application in many institutions and processes. Several methods are available to preserve microorganisms and include drying, lyophilization, cryopreservation and sub-culturing. Many of these methods, may lead to population change through selection, loss of viability as well as poor survival rates when used for maintenance of yeasts. In this study, different preservation methods (cryopreservation at -196°C in liquid nitrogen, freezing at -70°C and lyophilization) were compared in the maintenance of brewing inocula over a period of two years. Interestingly, a decrease in the percentage of variants and respiratory deficient yeasts (RDs) was generally found when preserved through cryopreservation (-196°C) and freezing (-70°C). In contrast, the percentage variants when revived yeasts were grown in wort, increased in yeasts maintained through lyophilization. A high percentage viable cells (>95%) was recorded for yeast cultures maintained at -196°C and at -70°C while viability was low (<50%) when maintained through lyophilization. Consequently, the maintenance methods of choice are cryopreservation and freezing. The developed cryopreservation method was successfully implemented in the brewing process that produced the champion lager beer "Castle Lager" at Burton-upon-Trent in the UK (April; 2000). The results of the estimate of the components of variance showed that the largest source of variation in all three of the methods tested, was the error arising from the analytical test. On the basis of these results, it , subsequently became another aim of this study to explore alternative analytical tests to differentiate and characterise yeasts in the brewing industry. Consequently, PCR based RFLP, fatty acid and sterol profiles were evaluated. Using PCR based RFLP, a study to differentiate brewing yeasts from related yeasts using amplification and restriction polymorphism of the ITS region was conducted. Differentiation was dependent on the restriction enzymes used to digest the amplified rDNA. Digestion with Hae 111,Cfo 1, Sau3 A1 and Msp 1 divided representatives of the genus Saccharomyces into several unique groups. With Msp 1 the DNA patterns for two brewing strains were similar, but could be differentiated from Sacch. cerevisiae and other species tested. It was also possible to distinguish some members of the Saccharomyces sensu stricto group i.e. Sacch. bayanus and Sacch. pastorianus from Sacch. cerevisiae and Saceh. paradoxus using Hae 111as well as Sacch. paradoxus from the other sensu stricto members using Msp 1 digestion. Fatty acid and sterol analyses were evaluated as alternative quality control methods to conventional differentiation and characterisation systems in the brewing industry. The presence of linoleic acid (18:2) in brewing yeast could be used to distinguish these from closely related yeast species. Furthermore, the absence of lanosterol and stigmasterol enabled differentiation of the brewing yeast from the rest of the closely related species tested. However, both fatty acid and sterol methods were not sensitive enough to detect mutants (variants) of brewing yeast. Conventional brewing identification tests proved superior to the above researched methods.

Tegnieke vir die bewaring van mikrobes is belangrik ten einde die beskikbaarheid van mikrobes vir aanwending in verskeie instansies en prosesse te verseker. Verskeie metodes vir die bewaring van mikrobes is beskikbaar en sluit in droging, vriesdroging, 'vries en die maak van subkulture. As hierdie metodes gebruik word vir die bewaring van giste, mag van hulle lei tot veranderinge in die populasie a.g.v. seleksie, verlies aan lewensvatbaarheid en lae oorlewingsvlakke. In hierdie studie is verskillende bewaringsmetodes (vries by (-196°Cin vloeibare stikstof, vries by -70°C en vriesdroging) vergelyk oor 'n tydperk van twee jaar in die bewaring van brou-inokula. Oor die algemeen is 'n afname in variante en respiratories-gebrekkige giste gevind as bewaring d.m.v. vriesing (-196°C en -70°C) gedoen is. In teenstelling, het die persentasie variante toegeneem as gevriesdroogde giste weer in moutekstrak opgegroei is. 'n Hoë persentasie lewensvatbare selle (>95%) is waargeneem in giskulture bewaar by -196°C en -70°C, terwyl lewensvatbaarheid laag was <50%) in gevriesdroogde kulture. Gevolglik is die beste bewaringsmetodes vriesing. Die ontwikkelde vriesingsmetodes is suksesvol geïmplementeer in die brouproses wat gelei het tot die produksie en kroning van die kampioen lager "Castle lager" by Burton-upon-Trent in die VK (April, 2000). Die resultate van die berekening van variasiekomponente het getoon dat die grootste bron van variasie in al drie die getoetste metodes, die fout a.g.v. die analitiese metode was. Op grond van hierdie resultate, het dit 'n verdere doel van die studie geword om ondersoek in te stel na alternatiewe analitiese metodes om giste in die brou-industrie te differensieer en te karakteriseer. Gevolglik is PKR gebaseerde RFLP, vetsuur- en sterolprofiele geëvalueer. Met behulp van 'n PKR gebaseerde RFLP, is 'n studie uitgevoer om brouersgiste van verwante giste te onderskei m.b.V. amplifisering en beperkings-polimorfisme van die ITS areas. Onderskeiding was afhanklik van die beperkingsensieme wat gebruik is om die geamplifiseerde rDNS te verteer. Vertering met Hae 111, Cfo 1,Sau 3A1 en Msp 1 het die verteenwoordigers van die genus Saccharomyces verdeel in verskeie unieke groepe. Met Msp 1 was die ONS patrone vir twee brouerstamme dieselfde, maar hulle kon onderskei ,word van Sacch. cerevisiae en ander getoetste spesies. Daar kon ook onderskei word tussen sommige lede van die Saccharomyces sensu stricto groep, nl. Sacch. bayanus en Sacch. pastorianus van Sacch. cerevisiae en Sacch. paradoxus m.b.v. Hae 111 en tussen Sacch. paradoxus en die ander lede van die sensu stricto groep m.b.v. Msp 1. Vetsuur" en sterolanalises is geëvalueer as alternatiewe kwaliteitsbeheermetodes vir konvensionele onderskeidings- en karakteriseringsisteme in die brou-industrie. Die teenwoordigheid van linoleïensuur (18:2) in brouersgiste is gebruik om hulle te onderskei van naby verwante spesies. Verder het die afwesigheid van lanosterol en stigmasterol dit moontlik gemaak om te. onderskei tussen brouersgiste en die ander getoetste naby verwante spesies. Beide die vetsuur- en sterolmetodes was egter nie sensitief genoeg om mutante (variante) van die brouersgiste waar te neem nie. Konvensionele brouersgis-identifikasietoetse het geblyk beter te wees as bogenoemde metodes.
Thesis (Ph.D. (Microbiology and Biochemistry))--University of the Free State, 2001
Keywords: Yeast; Microbial inoculants; Cultures (Biology) -- Cryopreservation; Fungi -- Collection and preservation